Study on the coordinated relationship between Urban Land use efficiency and ecosystem health in China. (March 2021) - Xie, Xue; Fang, Bin; Xu, Hanzeyu; He, Shasha; Li, Xin
Highlights: Provide a new idea for the relationship between urbanization and ecological environment. Considering the undesirable output, the land use efficiency is the highest in the east and the lowest in the middle. The areas with excellent ecosystem health are mainly distributed in the southwest. The coupling coordination effect decreases from the east coast and northwest to the inland. The distribution of coupling coordination effect is more similar to the distribution of land use efficiency. Abstract: China needs not only high land use efficiency, but also a high-quality ecological environment. Thus, clarifying interaction between land use efficiency and the ecosystem is crucial in accelerating China's new urbanization. In this study, therefore, we measured China's urban land use efficiency and ecosystem health to obtain the coordination effect between the two. Results showed that (1)from 2005 to 2018, China's urban land use efficiency slightly increased, and presented a decreased spatial trend from "East-West-Center". (2)The spatial pattern of ecosystem health was "high in the South and low in the North." Areas with an excellent ecosystem are mainly distributed through Southwest China.(3)The study found that most areas of China were in the process of slightly unbalanced to barely balanced development and presented decreases from the East Coast and Northwest to the Inland. Finally, this paper puts forward policy recommendations according to each region's coupling type.